Safety, efficacy, and pharmacokinetics of gremubamab (MEDI3902), an anti-Pseudomonas aeruginosa bispecific human monoclonal antibody, in P. aeruginosa-colonised, mechanically ventilated intensive care unit patients: a randomised controlled trial - Chastre, Jean; Francois, Bruno; Bourgeois, Marc; Komnos, Apostolos; Ferrer, Ricard; Rahav, Galia; De Schryver, Nicolas; Lepape, Alain; Koksal, Iftihar; Luyt, Charles-Edouard; Sanchez-Garcia, Miguel; Torres, Antoni; et al. (BMC, 2022)
Background: Ventilator-associated pneumonia caused by Pseudomonas aeruginosa (PA) in hospitalised patients is associated with high mortality. The effectiveness of the bivalent, bispecific mAb MEDI3902 (gremubamab) in preventing PA nosocomial pneumonia was assessed in PA-colonised mechanically ventilated subjects. Methods: EVADE (NCT02696902) was a phase 2, randomised, parallel-group, double-blind, placebo-controlled study in Europe,Turkey, Israel, and the USA. Subjects >= 18 years old, mechanically ventilated, tracheally colonised with PA, and without new-onset pneumonia, were randomised (1:1:1) to MEDI3902 500, 1500 mg (single intravenous dose),or placebo. The primary efficacy endpoint was the incidence of nosocomial PA pneumonia through 21 days post-dose in MEDI3902 1500 mg versus placebo, determined by an independent adjudication committee. Results: Even if the initial sample size was not reached because of low recruitment, 188 subjects were randomised (MEDI3902 500/1500 mg: n =16/87

placebo: n = 85) between 13 April 2016 and 17 October 2019. Out of these, 184 were dosed (MEDI3902 500/1500 mg: n =16/85

placebo: n = 83), comprising the modified intent-to-treat set. Enrolment in the 500 mg arm was discontinued due to pharmacokinetic data demonstrating low MEDI3902 serum concentrations. Subsequently, enrolled subjects were randomised (1:1) to MEDI3902 1500 mg or placebo. PA pneumonia was confirmed in 22.4\% (n =19/85) of MEDI3902 1500 mg recipients and in 18.1\% (n = 15/83) of placebo recipients (relative risk reduction {[}RRR]: - 23.7\%

80\% confidence interval {[}CI] - 83.8\%, 16.8\%

p =0.49). At 21 days post-1500 mg dose, the mean (standard deviation) serum MEDI3902 concentration was 9.46 (7.91) mu g/mL, with 80.6\% (n =58/72) subjects achieving concentrations >1.7 mu g/mL, a level associated with improved outcome in animal models. Treatment-emergent adverse event incidence was similar between groups. Conclusions: The bivalent, bispecific monoclonal antibody MEDI3902 (gremubamab) did not reduce PA nosocomial pneumonia incidence in PA-colonised mechanically ventilated subjects.
Keywords: Monoclonal antibody; Prevention; Pharmacokinetics; Pseudomonas aeruginosa ventilator-associated pneumonia; Safety